THIRTEEN FALLACIES ABOUT THE USERS AND USES OF ENGLISH AS AN INTERNATIONAL LANGUAGE - Guerra, Luis (2013)
Some applied linguists have provided a definition of English as an international language (EIL) in order to distinguish it from other concepts such as English as a foreign language (EFL) or English as a second language (ESL). Whereas EFL and ESL have usually been related to non-native speakers of English communicating with native speakers of English, English as an international language can be defined as “that English in all its linguistic and sociolinguistic aspects which is used as a vehicle for communication between non-native speakers only, as well as between any combination of native and non-native speakers.” (Campbell et al., 1983) In other words, EIL aims at mutual intelligibility and appropriate language use involving nationals of different countries. Essentially, the concept of EIL focuses on cross-cultural, cross-linguistic interactions. In order to identify the major features of EIL, Campbell et al. (1983) introduced three principles of teaching EIL (TEIL): (1) knowledge of the different social and cultural patterns and rules present in communicative exchanges involving speakers of more than one country or culture; (2) training native speakers in the use of English in international contexts; and (3) training non-native speakers in the use of language with native as well as with non-native speakers. This paper aims at dealing with some pedagogical implications of TEIL. In spite of recent changes in ELT, there are still some common ideas based on linguistic and pedagogical fallacies. Through the proposal of a TEIL paradigm, this paper will point out some of these fallacies hoping to generate ample debate on the new directions in ELT worldwide.